2018
DOI: 10.21897/rmvz.1242
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de Salmonella spp., en ganglios mesentéricos de porcinos en plantas de beneficio Colombianas

Abstract: Objective. To determine the prevalence of Salmonella spp., in pigs mesenteric ganglion, from different regions of Colombia. Materials and Methods. A stratified sampling by proportional fixation was carried out at benefit plants of each of the 13 participating departments, whose pork production volume is representative at national level. Sampling was performed during five months, for a total of 457 samples analyzed. Salmonella spp., identification was performed by the MDS Molecular System, later isolates were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Other studies in Colombia have reported a prevalence of Salmonella spp. of 3% in pig carcasses, 13% in environmental samples from slaughterhouses, and 28% in samples of pig mesenteric ganglia ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies in Colombia have reported a prevalence of Salmonella spp. of 3% in pig carcasses, 13% in environmental samples from slaughterhouses, and 28% in samples of pig mesenteric ganglia ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Salmonellosis in pigs is treated using antimicrobials including amoxicillin–clavulanic acid, ampicillin, ceftiofur, ciprofloxacin, chloramphenicol, florfenicol, gentamicin, sulfamethoxazole–trimethoprim, tetracycline, and macrolide antibiotics such as tilmicosin – many of these antimicrobials are important for human therapy ( 8 ). Antimicrobials are used in animals not only for treatment, but also for controlling the spread of infection (metaphylaxis), preventing infection (prophylaxis), improving feed efficiency, and promoting growth ( 9 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In 2020, 13.0% of the human cases of salmonellosis reported in the European Union (EU) were due to consumption of contaminated pork. In 2015, the Salmonella prevalence was 28.2% on pork carcasses at abattoirs in Colombia with S. Typhimurium, S. Agama and S. Agona being the main serotypes found (9). Comprehensive control of Salmonella throughout the food value chain can decrease the incidence of human salmonellosis (6,10,11).…”
mentioning
confidence: 99%